CircHIPK2 recruits SRSF1 to increase TXNIP mRNA stability and promotes autophagy-dependent ferroptosis and apoptosis in myocardial ischemia-reperfusion injury - Zhu Zhang; Jinqi Hao; Qinghong Qiao; Junting Song; Yanqin Yu (Journal of Cardiothoracic Surgery)
Abstract Background Myocardial ischemia/reperfusion injury (MIRI) secondary to acute myocardial infarction (AMI) can lead to cardiomyocyte death and impaired cardiac function. Studies have confirmed that circular RNAs (circRNAs) play an important role in MIRI. In this study, the role and mechanism of circHIPK2 in MIRI were evaluated. Methods Human cardiac myocytes (HCM) were cultured under Hypoxia/Reoxygenation (H/R) condition to establish a MIRI model in vitro. Expression of circHIPK2, SRSF1 and TXNIP was assessed using RT-qPCR. Protein levels of autophagy markers (LC3II/LC3I, Beclin1, p62) and ferroptosis markers (GPX4, FTH1, ACSL4) were detected by Western blot. Cell viability and apoptosis were assessed by CCK-8 and flow cytometry. Levels of oxidative stress markers (MDA, SOD) and inflammatory factors (IL-6, IL-1β, TNF-α) were tested by ELISA assay. Iron concentration was measured with an iron detection kit. Location of circHIPK2 in cells was detected by RNA-nucleosome separation assay. RIP and ChIP assays verified the relationship between circHIPK2, SRSF1 and TXNIP. TXNIP mRNA stability was dertermined by actinomycin D. Infarct area was examined by TTC staining in myocardial ischemia/reperfusion (I/R) mouse model. HE staining evaluated myocardial injury. Results CircHIPK2 was increased in H/R-induced HCM cells. CircHIPK2 downregulation suppressed oxidative stress, inflammatory factors and autophagy-dependent ferroptosis in HCM cells induced by H/R. Additionally circHIPK2 recruited SRSF1 to target TXNIP and stabilized TXNIP mRNA expression. We further demonstrated that TXNIP upregulation overturned the therapeutic effects of circHIPK2 silencing on H/R model cells. In vivo, downregulation of circHIPK2 improved myocardial dysfunction caused by I/R. Conclusion Our results demonstrate that circHIPK2 contributes to MIRI through inducing oxidative stress and autophagy-dependent ferroptosis via SRSF1/TXNIP axis, offering new insights into MIRI treatment.